Covalent organic frameworks embedded membrane via acetic-acid-catalyzed interfacial polymerization for dyes separation: Enhanced permeability and selectivity. (December 2020) - Wu, Chao; Wang, Xiaoping; Zhu, Tongren; Li, Pan; Xia, Shengji
Abstract: With the increasing demand of high water-quality, membrane filtration technologies are playing further important roles in water treatment owing to their small footprints, reduced use of chemicals and stable performances. However, the inherent permeability-selectivity trade-off is still a significant obstacle restricting the broad applications of membrane separation. Hydrophilic modification via doping nanoparticles into membranes is considered an effective solution to improve the permeability while maintaining selectivity. However, agglomeration of nanoparticles often results in inhomogeneity of the modified membranes. In this study, hybrid membranes with separated covalent organic framework (COF) particles that were uniformly embedded in the membrane surface pores were firstly fabricated via acetic-acid-catalyzed in situ synthesis. Owing to the ample hydrophilic chemical groups and tunable molecular transport channels in COFs, the modified membranes yielded almost twice higher water flux (about 200 L m −2 ·h −1 ·bar) than the pristine membranes with simultaneously enhanced rejection of water pollutants (i.e., dyes). In addition, the pure organic structure of COF improves the polymer-filler interaction of the mixed film, thereby reducing the risk of leakage. Therefore, the hybrid membranes also exhibited relatively high stability in long-term operations and different pH conditions, which makes them promising candidates in future membrane applications. Graphical abstract: Image 1 Highlights: The COFs were formed by quick acetic-acid-catalyzed in-situ synthesis. Membranes with separated COFs uniformly embedded in the surface pores were obtained. The hybrid membranes showed enhanced permeability and selectivity of dyes. The hybrid membranes showed stability in long-term operating and different pH.